2021
DOI: 10.1002/ange.202111052
|View full text |Cite
|
Sign up to set email alerts
|

Stable Super‐Resolution Imaging of Lipid Droplet Dynamics through a Buffer Strategy with a Hydrogen‐Bond Sensitive Fluorogenic Probe

Abstract: Although super‐resolution imaging offers an opportunity to visualize cellular structures and organelles at the nanoscale level, cellular heterogeneity and unpredictability still pose a significant challenge in the dynamic imaging of live cells. It is thus vital to develop better‐performing and more photostable probes for long‐term super‐resolution imaging. Herein, we report a probe, LD‐FG, for imaging lipid droplet (LD) dynamics using structured illumination microscopy (SIM). LD‐FG allows wash‐free imaging of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Under the STED laser intensity of 5 MW cm −2 , the STED imaging with gate delay times (tg) of 1 ns, 3 ns or 6 ns provided FWHM resolutions of 93 ± 9 nm, 60 ± 7 nm, or even up to 37 ± 4 nm (Figure 3D and Figure S17B). The resolution of 37 ± 4 nm is substantially broken the diffraction limit of light (~250 nm) and represents the highest resolution of fluorescence imaging of LDs up to date (Table S3) [11][12][13][14][15][16]. This is also a state-of-the-art resolution of living cell STED super-resolution imaging (Table S4) [33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Sted Super-resolution Imaging With Lipi-qamentioning
confidence: 91%
See 2 more Smart Citations
“…Under the STED laser intensity of 5 MW cm −2 , the STED imaging with gate delay times (tg) of 1 ns, 3 ns or 6 ns provided FWHM resolutions of 93 ± 9 nm, 60 ± 7 nm, or even up to 37 ± 4 nm (Figure 3D and Figure S17B). The resolution of 37 ± 4 nm is substantially broken the diffraction limit of light (~250 nm) and represents the highest resolution of fluorescence imaging of LDs up to date (Table S3) [11][12][13][14][15][16]. This is also a state-of-the-art resolution of living cell STED super-resolution imaging (Table S4) [33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Sted Super-resolution Imaging With Lipi-qamentioning
confidence: 91%
“…To visualize LDs and reveal their versatile functions, the confocal and wide-field fluorescence microscopies have been widely employed with sub-micrometer resolution (~250 nm) [6][7][8][9][10]. The emerging super-resolution fluorescence microscopies, such as stimulated emission depletion microscopy (STED) and photoactivated localization microscopy (PALM), successfully broke the resolution limit of light diffraction and make it possible to further visualize the small/nascent LDs with nanoscale resolution [11][12][13][14][15][16]. For example, our group developed a super-photostable LDs fluorescent probe Lipi-DSB for STED super-resolution imaging, successfully visualizing the nanoscale fusion process of nascent LDs [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 shrinkage and heterogeneity and composition variations. 32 Although various dynamics of LDs and their cytoplasmic functions have been thoroughly explored, the functions and changes of LDs in the nucleus are ambiguous. In 2019, Fujimoto et al reported that nuclear LDs in hepatocytes were derived from apolipoprotein B (ApoB)-free lumenal LDs by immunofluorescence microscopy costained with BODIPY 558 (commercial LD probe) and Hoechst 33342 (commercial nucleus probe).…”
mentioning
confidence: 99%
“…In recent years, the fluorescent probe has been extensively employed in biological detection and analysis due to its advantages of nondestructive in real time and in situ detection. Yu and co-workers reported a fluorescent probe for the simultaneous visualization of LDs and ER successfully by two different colors . In addition, Xu et al tracked various types of LD dynamics, such as growth and shrinkage and heterogeneity and composition variations . Although various dynamics of LDs and their cytoplasmic functions have been thoroughly explored, the functions and changes of LDs in the nucleus are ambiguous.…”
mentioning
confidence: 99%